Bajo el puente: escucha y traducción de Apollinire - Hernández Álvarez, Mª Vicenta (Anales de Filología Francesa, 2009)
“Le Pont Mirabeau” functions as a dynamic centre in the plurality of perspectives and readings in Apollinaire’s poetics. Painting (Cubism), poetry (Symbolism and Surrealism), and music (folk songs) structure this analysis which moves from looking to listening, passing through “l’énergie imitative” of his translations.